A narrative review of sleep deprivation in ultra-endurance cycling <subtitle>Improving mental health awareness and regulatory emphasis</subtitle> - Alexander Smith; Anna Buadze; Jill Colangelo; Michael Liebrenz (Hogrefe AG, 2023)
Abstract: Introduction: The popularity of ultra-endurance cycling is increasing. Amongst race participants, sleep deprivation and periods of intermittent or acutely short sleep are common. Scientific research has typically focussed on the physiological or competitive performance based impact of these sleep-related paradigms. However, there is limited evidence about the mental health effects of sleep patterns in ultra-endurance cycling, despite established links between sleep deprivation and psychiatric and psychological issues. Methods: We conducted a narrative review synthesising extant empirical literature about sleep deprivation in ultra-endurance cycling. Results: Based on our search criteria, seven papers were identified discussing sleep patterns in ultra-endurance races. Each of these indicate that sleep deprivation is a prominent aspect of ultra-endurance competitions, with varying implications for riders. Discussion: Using these findings, we highlight the possible mental health consequences of sleep deprivation in these races, with reference to general scientific literature and other ultra-endurance sports. We also advocate for increased knowledge exchanges, regulatory emphasis, and additional research. Conclusion: Sleep deprivation and extreme sleep patterns are a substantial issue in elite-level cycling competitions, raising potential mental health concerns. More attention to this topic is necessary amongst organisers, participants, researchers, and community-level platforms, like the Global Cycling Network.